Preservation of Archaeological and Natural Values. A Case Study of the North-Western part of Latvia - Sandra Zirne; Egita Lūsēna (Internet Archaeology, 2023)
The article is a review of specially designated nature protected areas and Stone Age settlements in north-western Latvia, called North Kurzeme. This area was chosen because it has a special environment. It is a culturally and historically important coastal region with diverse protected natural areas, a unique coastal landscape, and important archaeological sites. The article provides information about Moricsala Nature Reserve and Slītere National Park, their management, and about the Stone Age settlements discovered there.